An analysis of the public benefits test of the Bank holding company act - Jesse, Michael A.; Seelig, Steven A. (New York : Federal Reserve Bank of New York, 1974)
This article investigates the nature of public benefits required by the Board of Governors of the Federal Reserve System in connection with the applications of bank holding companies o acquire both banks and nonbanking firms
This paper is being circulated for purposes of discussion and comment only.
Includes bibliographic reference.
hza 28/01/2019
Loans
Keywords: Banking services